2020
DOI: 10.3390/tropicalmed5020051
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mosquito Bloodmeals Collected in Diverse Habitats in Malaysian Borneo Using COI Barcoding

Abstract: Land cover and land use change (LCLUC) acts as a catalyst for spillover of arthropod-borne pathogens into novel hosts by shifting host and vector diversity, abundance, and distribution, ultimately reshaping host–vector interactions. Identification of bloodmeals from wild-caught mosquitoes provides insight into host utilization of particular species in particular land cover types, and hence their potential role in pathogen maintenance and spillover. Here, we collected 134 blood-engorged mosquitoes comprising 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Brown et al (2018) amplified 38 blood meals from mosquitoes collected in Borneo from domestic, peridomestic, and forest land covers and identified two hosts, chicken (Gallus gallus) and Homo sapiens; the majority of blood meals were from Culex mosquitoes in domestic sites, with only four samples derived from palm and rubber tree plantations and none from forests (Brown et al 2018). In a separate study, we identified the hosts of five blood-engorged A. albopictus collected within oil palm plantations from the current study and three blood-engorged A. albopictus collected in forests from this study as well as in nearby forests in 2017: All were humans (Young et al 2020). Vector competence of A. albopictus for various arboviruses, and the impact of temperature on competence, has been tested in multiple studies (Alto and Bettinardi 2013, Vega-R ua et al 2015, Murdock et al 2017, Liu et al 2017, Alto et al 2018, Reinhold et al 2018.…”
Section: Mosquito Sex Ratio Between Interior Forest and Interior Oil Palmmentioning
confidence: 91%
“…Brown et al (2018) amplified 38 blood meals from mosquitoes collected in Borneo from domestic, peridomestic, and forest land covers and identified two hosts, chicken (Gallus gallus) and Homo sapiens; the majority of blood meals were from Culex mosquitoes in domestic sites, with only four samples derived from palm and rubber tree plantations and none from forests (Brown et al 2018). In a separate study, we identified the hosts of five blood-engorged A. albopictus collected within oil palm plantations from the current study and three blood-engorged A. albopictus collected in forests from this study as well as in nearby forests in 2017: All were humans (Young et al 2020). Vector competence of A. albopictus for various arboviruses, and the impact of temperature on competence, has been tested in multiple studies (Alto and Bettinardi 2013, Vega-R ua et al 2015, Murdock et al 2017, Liu et al 2017, Alto et al 2018, Reinhold et al 2018.…”
Section: Mosquito Sex Ratio Between Interior Forest and Interior Oil Palmmentioning
confidence: 91%
“…In our observation from the programmatic review, a dengue surveillance system is not capable enough to provide a timely alert for anticipating the outbreak. Many outbreak events were realized by the authority when lots of cases and deaths published on the news [9] [7].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, warmer temperatures accelerate the development of larvae, increase rates of YF viral replication, and aid in the wider dissemination of vectors such as Aedes and Haemagogus species [43][44][45]. Human behavior and alterations in land-use practices, including recent upticks in deforestation for agriculture, logging, and mining can culminate in the generation of new habitats for hosts and vectors, altering vector-host interactions, host utilization of particular species in particular land cover types, and thus their potential role in pathogen maintenance and spillover [44,46]. Although Hg.…”
Section: Factors Shaping Yfv Transmission Cyclesmentioning
confidence: 99%